PERRY'S CHEMICAL ENGINEERS' HANDBOOK - Perry, Robert H., 1924-1978, editor 409121; Green, Don W., editor 348392 (New York,NY : Mc Graw-Hill, 2008)
First published in 1934, Perry's Chemical Engineers' Handbook has equipped generations of engineers and chemists with an expert source of chemical engineering information and data. Now updated to reflect the latest technology and processes of the new millennium, the Eighth Edition of this classic guide provides unsurpassed coverage of every aspect of chemical engineering-from fundamental principles to chemical processes and equipment to new computer applications.